2006
DOI: 10.4049/jimmunol.177.12.8560
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine Stimulates IL-1β Release from Microglia via a P2X7 Receptor-Independent Mechanism

Abstract: IL-1β released from activated macrophages contributes significantly to tissue damage in inflammatory, degenerative, and autoimmune diseases. In the present study, we identified a novel mechanism of IL-1β release from activated microglia (brain macrophages) that occurred independently of P2X7 ATP receptor activation. Stimulation of LPS-preactivated microglia with lysophosphatidylcholine (LPC) caused rapid processing and secretion of mature 17-kDa IL-1β. Neither LPC-induced IL-1β release nor LPC-stimulated intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
66
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 60 publications
7
66
2
4
Order By: Relevance
“…LPC was recently reported to be a potent endogenous inducer of mIL-1␤ release in microglial cells (21). In agreement with this report, we demonstrated that LPC alone triggered the release of mIL-1␤ in mouse microglial cells.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…LPC was recently reported to be a potent endogenous inducer of mIL-1␤ release in microglial cells (21). In agreement with this report, we demonstrated that LPC alone triggered the release of mIL-1␤ in mouse microglial cells.…”
Section: Discussionsupporting
confidence: 81%
“…In agreement with this report, we demonstrated that LPC alone triggered the release of mIL-1␤ in mouse microglial cells. In primary microglia, the lower concentrations of LPC (20 -40 M) were able to generate a significant amount of mIL-1␤, suggesting that this event physiologically occurs during inflammation as described in a previous report (21). In contrast, we demonstrated the anti-inflammatory function of LPC by showing the inhibition of P2X7R-dependent mIL-1␤ release.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…7c). The change in IL-1β was consistent with previous studies, in which IL-1β was packaged in the bleb of MVs and secreted through the activation of P2X7 receptors [11,44]. However, the other two cytokines, TNF-α and IL-6, displayed no distinct changes.…”
Section: Discussionsupporting
confidence: 81%
“…In addition to AA, glycerophospholipid metabolism by PLA 2 s following stroke also elevate LPC levels in blood, cerebrospinal fluid, and brain tissue following ischemic and hemorrhagic stroke (61,62,79,164). LPCs act as potent mediators of inflammation in the brain following stroke via stimulated release of interleukin 1b (162) and subsequent activation of microglia (122,143).…”
mentioning
confidence: 99%